Improving performance of green innovation practices under uncertainty - Tseng, Ming Lang (Animo Repository, 2013)
Environmental issues have received substantial attention in corporate green operations. Environmental practices have been well studied but only a few studies have presented the green innovation practices of corporate firms. This study proposes to evaluate green innovation practices with a particular focus on the managerial, process, product and technology innovation aspects. This analysis focuses on Taiwanese printed circuit board manufacturing firms. Such a study does exist and the performance of the focal firm's green innovation activities has been evaluated. This study identified the appropriate green innovation aspects and criteria for the case firms and, subsequently, developed the following hybrid method: (i) evaluate the weights of the aspects and criteria as described by linguistic preferences; and (ii) use an analytical network process with entropy weights to evaluate the proposed framework. This study presents the evidence of green innovation practices and has interesting implications for operations management research and practices. This knowledge contributes towards decision-making and implementation of green innovation practices. © 2010 Elsevier Ltd. All rights reserved.